Redes sociales, literacidad e identidad (es): el caso de facebook - Vargas Franco, Alfonso (Colombian Applied Linguistics Journal, 2016)
This paper presents the first results of a study on the relationship between literacy practices and identity in the social network Facebook. In this study the role of literacy practices in the social network Facebook and how they affect the construction of individual and collective identities of the informants are analyzed. The author highlights the profound changes in modes of reading and writing as a result of digital technologies and social networks. The study also evidences how through multimodal discourses people construct their individual and collective identities. The corpus consists of in-depth interviews with two informants that were recorded and transcribed following the model of discourse analysis. The preliminary results of this qualitative-ethnographic study indicate that users of Facebook as a social network deploy an intense literacy activity with a strong identity component.